Mapeamento de processos e melhoria contínua: aplicação delean office em um departamento de seguros de uma cooperativa de crédito. - (:unkn) unknown (Universidade Federal do Pampa, 2025)
The pursuit of operational efficiency drives financial organizations, particularly credit cooperatives, to rethink their administrative processes in order to reduce waste and improve service quality. In this context, Lean Office emerges as a strategic approach to optimizing workflows and standardizing activities, thereby enhancing productivity and operational clarity. This study analyzed the insurance quotation process in a credit cooperative by applying Lean Office principles to identify inefficiencies and propose improvements. Characterized as a single case study with a qualitative and exploratory approach, the research employed direct observation, document analysis, and semi structured interviews with employees in the insurance department. The main methodological tool was Value Stream Mapping (VSM), which enabled a detailed visualization of process stages and facilitated the identification of inefficiencies, bottlenecks, and non-value-added activities. The results revealed critical issues such as high quotation lead time, rework caused by duplicated information, lack of standardized procedures, and absence of formal performance indicators. Based on this analysis, improvement proposals were developed grounded in Lean principles, including process standardization, workflow optimization, and the establishment of performance indicators, ensuring greater agility and operational efficiency. Considering the relevance of Lean Office in administrative process management, this study contributes to a deeper understanding and practical application of this approach within the insurance sector of credit cooperatives, providing strategic insights for organizational decision-making, fostering waste reduction, efficiency enhancement, and strengthening a culture of continuous improvement within the cooperative.
Keywords: Lean office; Mapeamento do fluxo de valor; Cooperativa de crédito; Gestão de processo; Melhoria contínua; Value stream mapping; Credit cooperative; Process management; Continuous improvement; ENGENHARIAS